Midwest Electric Art : A Short history. (Minneapolis : The Dolly Fiterman Art Gallery, 1980)
Jirka, Brad ; Andersen, Norman ; Jones, Katy ; Linell, David
Midwest Electric Art, The Dolly Fiterman Art Gallery, Minneapolis, 1980
boek